RANCANG BANGUN SISTEM PENGOPRASIAN MESIN UKIR BAKAR BERBASIS ARDUINO UNO MENGGUNAKAN SOFWARE ASPIRE - Rismawan, Roby Ahmad; Apnena, Riri Damayanti (Jurnal Mahasiswa Terapan, 2025)
This research focuses on the design of a combustion engraving machine operating system controlled by an Arduino Uno microcontroller and supported by Aspire software. This engraving machine is designed to facilitate engraving on various materials, wood with high precision and effective control. The Arduino Uno acts as the main controller that regulates the movement of stepper motors on the X and Y axes, as well as the burning intensity, according to the design pattern generated by the Aspire software. The design process starts with the mechanical design of the machine, which allows flexibility and accuracy in the engraving process. The Aspire software is used to design the engraving patterns which are then converted into G-codes that can be processed by the Arduino Uno. This code is used to control the movement of the motor and burner module so that the engraving results match the desired design. The test results show that the designed system is able to perform its duties efficiently, producing detailed and consistent engravings.